Variability and Variation in Second Language Acquisition Orders: A Dynamic Reevaluation. Issue 1 (March 2015) - Lowie, Wander; Verspoor, Marjolijn; Hulstijn, Jan H.; Ellis, Rod; Eskildsen, Søren W.
<x xml:space="preserve">Abstract</x> The traditional morpheme order studies in second language acquisition have tried to demonstrate the existence of a fixed order of acquisition of English morphemes, regardless of the second language learner's background. Such orders have been taken as evidence of the preprogrammed nature of language acquisition. This article argues for a process‐based, dynamic explanation of development, in which each developmental step is based on the dynamic interaction of all processes involved. Due to the complexity of these interactions, the developmental process cannot be predetermined and fixed. Although stages of development like the acquisition order of morphemes are commonly observed as a grand sweep effect at the group level, these stages may be meaningless at the level of the individual language learner. This paradox shows we can only make the observations that our method allows us. If we are interested in grand sweep effects that may be generalizable to large populations of learners, we will have to carry out group studies with representative samples that can be analyzed using Gaussian statistics based on the normal distribution. But if we are interested in how an individual learner progresses over time as a result of changing variables in a changing context, we will have to conduct longitudinal studies and use nonlinear methods of analysis.